Characteristics and Outcomes of Patients with Pelvic Organ Prolapse: an Analysis of Data from Mulago National Referral Hospital from 2007–2016 - Byamugisha, Josaphat; Barageine, Justus; Kakaire, Othman; Nalubwama, Haddy; Obore, Susan; Mukasa, David Christopher; Mwanje, Haruna; Alia, Godfrey; El Ayadi, Alison (African Health Sciences, 2023)
Pelvic organ prolapse (POP) is associated with negative physical, social, psychological, and sexual experiences. There is paucity of data in low and middle income countries like Uganda. The purpose of this study was to describe clinical characteristics and outcomes of patients undergoing surgery for POP from 2007 to 2016. The study was conducted at Mulago National Referral Hospital from 2014 to 2016. We conducted a retrospective review of the urogynecology surgical records using a standardized medical record abstraction form. Data of 222 POP patients were abstracted and managed using REDCap. Analysis was performed using Stata statistical software, v14. The mean participant age and parity was 57 years and 7 respectively. Ninety four percent of participants presented with a mass protruding from the vagina, 38% with uterine prolapse and 32% with cystocoele. Anaemia and hypertension were common comorbidities. Women underwent a variety of surgery types, and 35% experienced persistent pain post-operatively. At hospital discharge, 83% had achieved either complete resolution or improvement in their condition. Measures encouraging presentation for care as soon as symptoms are experienced and reduction of total fertility rate will be beneficial. Patients with POP should be routinely screened for anaemia and hypertension.